“Personally, I feel sorry, but professionally, I don't have a choice.”1 Understanding the drivers of anti-Roma discrimination on the rental housing market - Váradi, Luca; Szilasi, Blanka; Kende, Anna; Braverman, Jeremy; Simonovits, Gábor; Simonovits, Bori (Frontiers in Sociology, 2023)
The aim of our study is to assess the drivers of discriminatory behaviors of real-estate agents and private landlords toward prospective Roma tenants, relying on qualitative data from Hungary. Though there is a broad literature on the forms and frequency of discrimination, we know much less about the question of why people discriminate. Previous research suggests that discrimination on the basis of ethnicity is widespread in Hungary. To understand the drivers of discrimination, we analyzed: (a) the sources and justifications of discrimination of Roma people on the rental housing market among real-estate agents and private landlords, the actors making decisions about tenants (b) mapped the social embeddedness of discrimination, and (c) assessed the resilience of discriminatory intentions by analyzing the reactions to a 3-min advocacy video showing discrimination of Roma people on the rental housing market. We conducted and analyzed five online group discussions with 18 real estate agents and landlords advertising properties for rent in different regions of the country. Our qualitative study revealed that discrimination of Roma people is understood to be a widespread and socially acceptable practice driven by the need to avoid risks attributed to Roma tenants based on widely held stereotypes about them. We identified certain specificities in the justification and argumentation strategies of real-estate agents in comparison to private landlords. By providing counter-information presenting the perspective of Roma tenants, negative views could be challenged on the emotional level and also by shifting the group dynamics, strengthening the viewpoint of those without prejudice. We discuss our findings with regards to the possibilities of interventions against discrimination in societies in which neither social norms nor state institutions expect the equal treatment of the members of ethnic minority groups.